Checking the feasibility of utilizing pectin as a stabilizer in ˜Bhapa dahi - Patel, Ronak Amrutbhai; AH, Jana; AC, Patel; G, Gopi Krishna; PA, Suvera; ND, Joshi (Indian Journal of Dairy Science, 2022)
The investigation was carried out to check the feasibility of utilizing the pectin as stabilizer in Bhapa dahi. Bhapa dahi was prepared adopting the process standardized by Patel et al.(2016) employing thermophilic starter culture. A blend of chakka and sweetened condensed milk (SCM) [1:1 w/w] served as the base mix; optimum steaming period was 15 min. The mango pulp was added at the rate of 18% of the base mix. The moisture, fat on dry matter (FDM), protein and pH of mango Bhapa dahi were 52.48-52.72%, 15.69-15.72%, 7.83-7.89% and 5.18-5.19 respectively. Bhapa dahi samples had compositional values that were similar to values laid down by FSSA for fruit shrikhand. On the basis of the findings of the experiment, it was decided not to utilize pectin in the formulation of Bhapa dahi, since it exerted some adverse impact on the flavour and body and texture of product. Bhapa dahi made without pectin had highest sensory score of 92.68 (0.0% pectin), 89.93 (0.1% pectin) and 88.65 (0.2%) (Out of 100).Â